Mobile emergency advisor application based on extreme project management approach [electronic resource] - Chu, Wei Ching, 1986-; Ahmad Zaki Abu Bakar, supervisor (2014)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2014